Penerapan Etika Dan Moral Pada Alumni Pondok Pesantren Al Falah Putera Banjarbaru - Muhammad Irpansyah; Nurul Qomariyah (STAI AL FALAH Banjarbaru, 2020)
This study discusses the application of ethics and morals of the alumni of the Al Falah Putera Islamic Boarding School Banjarbaru. The formulation of the problem in this study is how to apply the ethics and morals of Al Falah Putera Islamic Boarding School alumni to teachers, parents and friends. Data were collected by using observation, interview, questionnaire and documentation techniques. Based on the results of the study, it is known that alumni apply their ethics and morals to teachers by greeting first when meeting teachers, keeping talking to their teachers, maintaining attitudes and behaviour. The ethics and morals of students towards parents are listening and carrying out parental orders, humbling themselves to both parents, soft words and polite speech, not looking at them with cynicism and permission before travelling. Ethics and morals of students towards friends by prioritizing help to friends, keeping secrets of friends, speaking well and politely, listening to every word he says, and having a sense of affection. So it can be concluded that the application of ethics and morals of the alumni of the Al Falah Putera Islamic Boarding School Banjarbaru towards teachers, parents, and friends is good. Keywords: Ethics, Morals, Islamic Boarding School.